MODEL FOR AUCTION WITH INCENTIVE FROM BAILOUT FUND ON SUGAR AUCTION - JAYA WICAKSONO (NIM23411061); Pembimbing: Dr. Andi Cakravastia Raja, S.T., M.T., ANDUNG
Since 2004, indonesian government has released farmer protection price policy (HPP) to prevent sugar farmer from financial loss in harvest season. This policy also means to increase farmers enthusiasm in cultivating sugar cane and raise up sugar production and productivity. However, along its implementation, this policy also led high retail sugar price driven by higher upstream price. Bailout agreements with private investor alleged to be significant cause of its high price. Sugar price level is mostly determined by auction mechanism. This study aims to learn how the additional incentive which received by bidder influence the auction price. In addition, as proposed to improve the mechanism of sugar auction, the auction will be analyzed how if bailout scheme using interest scheme. Auction price is obtained by using Monte Scarlo simulation. To get Random number, this simulation uses Linear Congroential Generator (LCG). Price simulation performed on two models, incentive model and interest model. The number of bidders, government HPP, cost of production, interest rate charged to farmers, and the profit margins of farmers and bidders would affect the result of simulations. Simulation results indicate that acution with incentive provide higher auction prices than without incentive. In the second model, simulation results give lower prices than current price. On the certain conditions and scenarios, these results also provide profitable price to producers and bidders. Based on the results of simulation, there are several alternatives could be done to decrease sugar price level such as moving source of bailout fund to independent institution, using interest rate system, and adjusting the government HPP according to pruducers cost or regions.